Investigating the factors influencing the attitudes of students toward the study of mathematics - Amoah, Charles; Adu-Gyamfi, Richmond; Mifetu, Romuald Koffi (Univeritas Papua, 2023)
The purpose of the study was to investigate the factors influencing the attitude of students towards the study of mathematics in selected Junior High Schools in Asokore in the Sekyere East District of the Ashanti Region of Ghana. The study was based on the ABC Attitude Model. Random sampling was used to select 102 respondents (students) in Asokore in the Sekyere East District for the study. A questionnaire was the sole instrument employed in the study. Descriptive statistics were used to analyze the data. It was found that school administrators and the mathematics teachers in JHSs in Asokore in Sekyere East District are doing well to motivate students’ to improve their achievement in mathematics, whereas most parents are not complementing the effort of the schools and the teachers by providing for their wards needs and encouraging them to learn mathematics. It was also found that even though most students agreed that mathematics is useful even at work places, they still think that mathematics is boring and makes them nervous, and therefore do not like to learn it. In addition, it was established that mathematics is not the students’ favorite subject; therefore, they do not like mathematics classes and solving mathematics questions.